Master class with Denis Zhdanov - Haydn, Joseph 1732-1809; Haydn, Joseph 1732-1809 (IClassical Academy, 2014)
Award-winning Siberian cellist Denis Zhdanov works with Dmitry Silvian on the second and third movements of Haydn's Cello Concerto No. 2 in D major in a master class at the Villa Sandra Lesa. Haydn composed his Cello Concerto No. 2 in D Major while serving as Kapellmeister for the Hungarian prince Nikolaus Esterházy. With a wealthy and encouraging patron, the composer found himself free to innovate, and one of those innovations was the elevation of the cello from bowed continuo instrument to melodic soloist. With Antonín Kraft, a talented virtuoso on the cello, also in the Prince's employ, Haydn wrote a lyrical yet technically-challenging concerto that cellists continue to treasure